Wpływ zagranicznych doświadczeń na budowę systemu ubezpieczeń w polskim rolnictwie - Obstawski, Zdzisław (The Influence of Foreign Experience on the Structure of System of Insurance in Polish Agriculture, 2005)
Analysing the presented ideas, the author thinks that the most efficient idea may be the one which establishes a system that includes mutual insurance societies with participation of the state (or the European Union) as a partial reinsurer. The studies prove the readiness of agricultural producers groups to possess the knowledge concerning the insurance market in agriculture particulary organizing mutual insurance societies. The scale of threats and the influence of the world economy liberalization will force the efforts to organise global (exemplary) models of risk management in agriculture. Beyond doubt, the process of the European integration predestinates the Union's states to take this task and create condition of common insurance programme supported from the Union's budget.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 138-143